Access to rehabilitation services for older adults living with dementia or in a residential aged care facility following a hip fracture: healthcare professionals' views. Issue 6 (12th March 2021) - Mitchell, Rebecca; Fajardo Pulido, Diana; Ryder, Tayhla; Norton, Grace; Brodaty, Henry; Draper, Brian; Close, Jacqueline; Rapport, Frances; Lystad, Reidar; Harris, Ian; Harvey, Lara; Sherrington, Cathie; et al.
Abstract: Purpose: To enhance understanding of access to rehabilitation services in Australian and New Zealand acute care facilities for older adults living with dementia and/or living in residential aged care facilities (RACFs) following a hip fracture. Methods: Information on hip fracture rehabilitation was obtained from an online survey of 40 health professionals who were members of the Australian and New Zealand Hip Fracture Registry Network. This information was supplemented with key informant interviews with five geriatricians and five rehabilitation physicians. Results: Availability of hip fracture rehabilitation services differed by region and country. Around one in 10 respondents indicated that their facility had specific rehabilitation protocols for people living in RACFs or who were living with dementia. Barriers to providing hip fracture rehabilitation were commonly related to availability of resources. Rehabilitation pathways were determined according to individual patient characteristics and perceived potential benefit. Decision making was mainly informed by the patient's pre-fracture morbidity and residence. Three key themes and nine sub-themes emerged from the interviews. Conclusions: The development of consistent decision criteria and pathways for access to hip fracture rehabilitation could provide a standard approach to access to rehabilitation, particularly for patients with cognitive impairment and/or who reside in RACFs. IMPLICATIONS FOR REHABILITATION: Need to establish evidence-based criteria for patients who will benefit from hip fracture rehabilitation. Consistent decision criteria for access to hip fracture rehabilitation will assist in guiding a standard approach to providing rehabilitation, particularly for patients with cognitive impairment and/or who reside in RACFs. There is a need to ensure the availability of physiotherapy services in RACFs to assist with rehabilitation provision. Rehabilitation provided to patients with cognitive impairment and/or who are living in RACFs should be tailored to their physical and mental ability.